Analysis of siltation temporal variability in Foum Elgherza dam, province of Biskra (Algeria) - Khentouche, Adel; Dridi, Hadda (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value="{"1":2,"2":"The majority of dams in Algeria have some thirty years lifetime, when it comes to tanks intended for drinking water supply or irrigation whose socioeconomic interests justify an unlimited service guarantee. It matters to predict the water retention filling rate and protect these dams from siltation that seems very acute. This paper deals with the problem of siltation in Foum Lgherza dam, in the East Algeria. We attempt to identify siltation behavior according to a detailed analysis based on the comparative approach between results obtained by a projected relationship for the study area, and the measuring results obtained by bathymetric surveys, both of results are very close and determine the aggressiveness of erosive balance and accelerated siltation."}" data-sheets-userformat="{"2":15233,"3":{"1":0},"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">The majority of dams in Algeria have some thirty years lifetime, when it comes to tanks intended for drinking water supply or irrigation whose socioeconomic interests justify an unlimited service guarantee. It matters to predict the water retention filling rate and protect these dams from siltation that seems very acute. This paper deals with the problem of siltation in Foum Lgherza dam, in the East Algeria. We attempt to identify siltation behavior according to a detailed analysis based on the comparative approach between results obtained by a projected relationship for the study area, and the measuring results obtained by bathymetric surveys, both of results are very close and determine the aggressiveness of erosive balance and accelerated siltation.